PENGEMBANGAN BUDAYA ORGANISASI DAN SUMBER DAYA MANUSIA DALAM PERSPEKTIF MANAJEMEN STRATEGIK - Mauris, Novita; Hadiyati, Ernani; Nasir, M. Jamal Abdul (Universitas Bina Taruna Gorontalo, 2025)
This study aims to understand the plan strategy Permata Mojokerto Foundation in building an organization and strategies that are organization programs in developing human capital and implementing it. This study is a qualitative study using a data collection method that uses primary data from observations, interview, and documentation. Data types and data source originate from documentation and are analyzed in accordance with research objectives before comparing research findings using metrics. Data analysis techniques include data reduction, data mapping, and conslusion. The results of the study indicate that the strategy for Permata foundation has been successfully implemented by enhancing the quality of human resources in the aforementioned foundation. The culture of organizations based on the seven character that serves as distinctive features can also be implemented successfully. A few things A few things that should be noted are the program's implementation guidelines and evaluation methods. Therefore, Permata foundation must carry out strategic tasks like reaffirming existing formulation of vision and mission, increasing the use of information systems in all program components, assisting various staff members in evaluating decision, and creating more detailed program descriptions for human capital development.